2007
DOI: 10.1210/jc.2005-2720
|View full text |Cite
|
Sign up to set email alerts
|

Parturition Itself Is the Basis for Fetal Adrenal Involution

Abstract: Involution of the adrenal is faster than previously reported and, regardless of gestational age, occurs within the first week of life in terms of hormone secretion and within 2 wk in adrenal size. Involution involves a decline in DHEA-S but also in androstenedione and cortisol secretion, with a change in enzymatic activity. Males and females differ in their androstenedione levels and enzymatic activity. Parturition itself is the basis for fetal adrenal involution, supporting a key role for placental factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…Results of such studies also prove a dynamic increase in adrenal gland weight and their sudden involution in neonates [25][26][27][28][29].…”
Section: Adrenal Weight During Human Ontogenesismentioning
confidence: 78%
See 1 more Smart Citation
“…Results of such studies also prove a dynamic increase in adrenal gland weight and their sudden involution in neonates [25][26][27][28][29].…”
Section: Adrenal Weight During Human Ontogenesismentioning
confidence: 78%
“…Moreover, not gestational age but parturition itself is the basis for fetal adrenal involution [29]. This implicates that placental factors are also involved in maintaining the fetal adrenal.…”
Section: Factors Regulating Human Fetal Adrenal Growth and Steroidogementioning
confidence: 99%
“…The triggering mechanism for this rapid, profound change in adrenal morphology, cellular architecture, and steroidogenesis is not known. It has been suggested that the involution of the fetal adrenal is more related to gestational age than to timing Articles after birth (19), but more recent studies indicate that parturition itself triggers fetal adrenal involution, which was interpreted as suggesting that the withdrawal of a placental factor stimulated the onset of fetal adrenal apoptosis (20). We hypothesize that the transition from intrauterine hypoxia to extrauterine normoxia is also a key event in triggering the remodeling of the fetal adrenal.…”
mentioning
confidence: 77%
“…Therefore, we and others have hypothesized that the involution of the fetal adrenal is not "programmed" but "triggered. " A current view is that the trigger is the loss of placental hormones and growth factors (20). Such a trigger could also be secondary to the profound environmental change that accompanies birth.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a centrally positioned fetal zone, responsible for androgen production during pregnancy, disappears during the postnatal period. In newborns, dramatic shrinkage of adrenal glands takes place due to involution of the fetal zone caused by apoptotic cell death (4,8). In rodents, as short gestational period species, adrenal glands synthesize glucocorticoids and aldosterone, but they are unable to produce androgens (9).…”
Section: Kratak Sadr`ajmentioning
confidence: 99%